成型辊装置与受力机理分析 - 姜桂荣; 张树存 (Jixie chuandong)
The structure design of the forming roller device was introduced and the force-mechanism of the roller head was analyzed. The basic train of thought for roller shape design was given, reference basis to lengthen the service life of the forming roller was offered. In application, the forming roller of the structure and shape were testified to its simplicity, rationality, reliance, long service life and much higher qualification rate.